Does corporate social responsibility reporting enhance shareholders’ value? - Rashid, Afzalur (Journal of financial reporting & accounting, 2018)
Purpose This study aims to examine whether corporate social responsibility (CSR) and relevant reporting enhances firms’ economic performance among the listed firms in Bangladesh. Design/methodology/approach This study uses a content analysis to examine specific CSR-related attributes from 115 non-financial publicly listed firms in Bangladesh. Firm CSR reporting is evaluated against accounting and market performance measures, with a simultaneous equation approach used to control the potential endogeneity problem. Findings This study finds that CSR reporting significantly influences firm performance under both performance measures, although a firm’s economic performance does not influence CSR reporting. Research limitations/implications This study is subject to some limitations, such as the subjectivity or judgement associated in the coding process. Practical implications The findings imply that although CSR reporting by firms in Bangladesh is discretionary in nature, the ones that report add value to their firm. Originality/value This study contributes to the literature on the practices of CSR reporting in the context of the developing countries.